ANALISIS PROCRUSTES PADA INDIKATOR INDEKS PEMBANGUNAN MANUSIA (IPM) DI KABUPATEN/KOTA PROVINSI JAWA TENGAH (STUDI KASUS IPM TAHUN 2008 DAN 2013) - Bunga Maharani; Moch. Abdul Mukid; Suparti Suparti (Jurnal Gaussian, 2015)
Human Development Index (HDI) as a measure of development in the performance of a whole formed through the approach of the four indicators which is real expenditure per capita, the average length of school, literacy rates and life expectancy. To learn about how the in contributing each indicators need to be identified the changes that occurred. Of the changes can use these as an ingredient of analysis in order to cope with or reduce the problems of development to realize the quality sustainably. Hence, this study aims to know of the changes of HDI in Central Java by mapping position of districts there are into a map geometry resulting from metric multidimensional scaling analysis. Where in 2008 as the beginning of leadership and 2013 as the end of leadership of Provincial Governor of Central Java Mr. Bibit Waluyo for five years served. By using an analysis procrustes, obtained the results that in the early period and the end of having the consistency of 90,53 %. In other words, the similarity of the large this indicates that at the beginning and end leadership of relatively no change.Keywords: Indicator, Map geometry, Metric multidimensional scaling, Changes analysis procrustes.